2019
DOI: 10.1055/s-0039-1694967
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Paranasal Sinuses: A Single Center Experience

Abstract: Objective Squamous cell carcinoma (SCC) of the paranasal sinuses is usually diagnosed at an advanced stage, making curative therapy difficult. The goal of this study was to evaluate the management and outcomes of patients with SCC treated at our institution. Methods In a population-based consecutive prospective cohort, we conducted an analysis of all patients treated for SCC between 1988 and 2017. Results A total of 72 patients were included, follow-up was 100%. Mean follow-up was 57 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…found that close or positive margins within the PPF or ITF were associated with worse 5‐year RFS (hazard ratio [HR] 6.158, p = 0.001) and OS (HR 21.961, p = 0.006) 191 . Similar effects were reported by Konig et al., where retromaxillary involvement was associated with worse survival at 2, 5, and 10 years (35%, 29%, and 17%, respectively) 193 . In contrast, others found that PPF or ITF involvement was not an independent risk factor for worse outcome when compared to T4b tumors 194 .…”
Section: Resectabilitysupporting
confidence: 72%
“…found that close or positive margins within the PPF or ITF were associated with worse 5‐year RFS (hazard ratio [HR] 6.158, p = 0.001) and OS (HR 21.961, p = 0.006) 191 . Similar effects were reported by Konig et al., where retromaxillary involvement was associated with worse survival at 2, 5, and 10 years (35%, 29%, and 17%, respectively) 193 . In contrast, others found that PPF or ITF involvement was not an independent risk factor for worse outcome when compared to T4b tumors 194 .…”
Section: Resectabilitysupporting
confidence: 72%
“…[ 1 ] The most common histologies are squamous cell carcinoma followed by adenocarcinoma and adenoid cystic carcinoma etc. [ 15 16 17 18 19 20 21 ] Early staged tumours can be managed endoscopically[ 22 23 ] whereas open surgical approaches such as craniofacial resection, maxillectomy, midface degloving, lateral rhinotomy, and orbital exenteration deemed necessary for advanced tumours. It is quite challenging to perform surgery with clear margins due to complex anatomy of the region,[ 24 25 26 27 ] and hence, adjuvant radiotherapy becomes a very useful treatment modality in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Employment of systemic therapy for locally advanced disease could result in better outcomes and optimize the therapeutic armamentarium ( 33 ). Post-operative adjuvant therapy has a well-established role in the treatment of most craniofacial malignancies ( 34 37 ). The National Comprehensive Cancer Network suggested that adjuvant therapy should be applied except for T1 stage patients ( 38 ).…”
Section: Discussionmentioning
confidence: 99%